2020
DOI: 10.3233/atde200159
|View full text |Cite
|
Sign up to set email alerts
|

Motion Behavior and Range of Motion when Using Exoskeletons in Manual Assembly Tasks

Abstract: Although the automation level is high within the automotive industry, there are still a large number of manual tasks, especially is the final assembly of the vehicle. Overhead assembly operations is an example of a problematic manual task that can cause workers to develop musculoskeletal disorders in the shoulder complex. Exoskeletons may be a solution to reduce the risk for developing musculoskeletal disorders from the work tasks. This study evaluates and compares how the use of three different passive upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…According to the recent review by Moeller (2022) [ 19 ], studies examining the effects of EXOs in occupational settings mostly focus on passive EXOs, primarily investigating muscle activity (shoulder, upper limb, and body) and secondarily exploring other kinematic, physiological, or usability parameters. According to the review, the Paexo device has been considered in three studies [ 28 , 29 , 30 ], which demonstrated (in lab assessment) its effectiveness in reducing shoulder muscle activity without negatively impacting trunk activity or compromising performance, eliciting favorable judgments from users.…”
Section: Discussionmentioning
confidence: 99%
“…According to the recent review by Moeller (2022) [ 19 ], studies examining the effects of EXOs in occupational settings mostly focus on passive EXOs, primarily investigating muscle activity (shoulder, upper limb, and body) and secondarily exploring other kinematic, physiological, or usability parameters. According to the review, the Paexo device has been considered in three studies [ 28 , 29 , 30 ], which demonstrated (in lab assessment) its effectiveness in reducing shoulder muscle activity without negatively impacting trunk activity or compromising performance, eliciting favorable judgments from users.…”
Section: Discussionmentioning
confidence: 99%
“…By using the Airframe Exoskeleton, McFarland et al ( 2022) reported a higher minimum shoulder elevation, a higher mean forearm pronation and a lower shoulder axial rotation angel. Furthermore, when comparing three different exoskeletons (ExoVest, Paexo Shoulder, Mate), the movement while wearing the Mate exoskeleton deviates most from the movement without exoskeleton in the shoulder joint (Perez Luque et al, 2020).…”
Section: Kinematic and Kinetic Effects Of Exoskeleton Usementioning
confidence: 98%
“…Furthermore, when comparing three different exoskeletons (EksoVest, Paexo Shoulder, Mate), 12 participants rated the Paexo and nine participants the ExoVest as the best supporting system for OHW. No participant voted in favour of the Mate Exoskeleton (Perez Luque et al, 2020). In another laboratory study (Daratany and Taveira 2020), the participants rated the usefulness of the exoskeleton at the overhead workstation (WS) after 8 min of use with 4-5.5 points on a 7-point scale.…”
Section: Effects Of Exoskeleton Use On Subjective Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of exoskeletons can allow for more flexibility and efficiency in manual work tasks, reduce work-related injuries, and can also help overcome one of the major challenges in the western industry today, namely that of a changing demographic and an ageing workforce [2]. The current status of this technology is not however without challenges as they often limit the range of motion, cannot fully cope with a huge diversity of anthropometrics, and can, if not used properly, result in pressure injuries [9].…”
Section: The Operator 40 -Typologymentioning
confidence: 99%